2021
DOI: 10.1002/cyto.a.24300
|View full text |Cite
|
Sign up to set email alerts
|

Platelet mass cytometry: Optimization of sample, reagent, and analysis parameters

Abstract: Platelets mediate key biological processes, including hemostasis, immunity, and inflammation. Although platelets are often treated as a homogeneous cell population, they are known to be heterogeneous in size, age, surface receptor expression, and response to agonist stimulation, raising the possibility that distinct platelet subsets perform specialized functions and that such subsets may be altered in disease settings. Attempts to identify platelet subsets by flow cytometry have had limited success due in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Given that a previous study has shown a subset of platelets that are packaged with tissue factor to facilitate coagulation, whether these same cells also go on to become procoagulant has not yet been explored although it seems likely given the shared function, that these same cells may go on to become procoagulant 46 . Undoubtedly there are further biomarkers to be described and this may be where the platform of CyTOF supersedes fluorescent flow cytometry as many more parameters can be simultaneously screened 24–26 . However, where single‐parameter platelet fluorescent flow cytometry is performed diagnostically this could be expanded to include panels of markers described here, allowing further aspects of platelet function to be examined within the clinical setting without requiring the additional complexity of CyTOF 47 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given that a previous study has shown a subset of platelets that are packaged with tissue factor to facilitate coagulation, whether these same cells also go on to become procoagulant has not yet been explored although it seems likely given the shared function, that these same cells may go on to become procoagulant 46 . Undoubtedly there are further biomarkers to be described and this may be where the platform of CyTOF supersedes fluorescent flow cytometry as many more parameters can be simultaneously screened 24–26 . However, where single‐parameter platelet fluorescent flow cytometry is performed diagnostically this could be expanded to include panels of markers described here, allowing further aspects of platelet function to be examined within the clinical setting without requiring the additional complexity of CyTOF 47 …”
Section: Discussionmentioning
confidence: 99%
“…Automatic compensation was performed with VersaComp antibody capture beads and CytExpert (v2.1). Antibodies were used at optimal titers, and assays were designed according to platelet flow cytometry guidelines 26,32,33 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with low platelet counts, the best option consists of flow cytometric assays of platelet activation markers. The use of flow cytometry has some advantages: a smaller volume of blood is needed without platelet-rich plasma preparation [77,[80][81][82]. Several flow cytometry approaches have been successfully used in patients with severe chronic immune thrombocytopenia, showing that impaired platelet function is associated with bleeding, independent of platelet count.…”
Section: Main Techniques To Monitor Platelet Functionmentioning
confidence: 99%
“…We and others have used conventional flow cytometry to analyze single synaptosomes, but with limited multiplexing, and challenged by simultaneous detection of multiple small events [4,5,13,14]. Recently, we adapted mass cytometry (CyTOF) to the analysis of single human synaptosomes (SynTOF) to increase multiplexing capacity many fold [3]; others have used CyTOF to investigate different anuclear particles, platelets [15,16]. Here, we sought to improve SynTOF by adapting commercially available masstag cell barcoding (MCB) reagents, expecting that more metal bound per particle might enhance detection of smaller events.…”
Section: Introductionmentioning
confidence: 99%